NEUROSCIENCE AND THE SEVEN KNOWLEDGES: THE FORCE OF THE FUTURE - Pizano Chávez, Guillermina (2014)
The study of neuroscience and the seven knowledges has as a main objective to introduce neuroscience as a new paradigm which analyses and explains the intelligent human behavior. New researches in this area have brought investigation subjects in the theory and practice of the Education field. The neuroscience offers new explanations about knowledge related to conditions under which the learning process could be more effective. Also, neuroscience will enable us to establish the design of non conventional strategies in order to achieve the development of the intelligence and memory. It is in this context that the seven knowledges are introduced by Edgar Morín, who essentially states important problems which have been completely ignored and forgotten although they are necessary in order to achieve a successful teachinglearning process in this century. These seven knowledges should be analyzed in every culture or society. Furthermore, the theory which supports this text, defines the human condition not only as temporary but also as relevant in order to solve the mysteries of the universe and the human being